The influence of religio-spiritual insights and advertising antecedent factors on the advertising attitude of Muslim consumers in Indonesia during religious festival - Faisal Abyan Hakim; Nissa Ghulma Ratnasari (Journal of Socio-Cultural Sustainability and Resilience, 2026)
Background: The delivery of an advertisement is crucial, as advertisements aim to attract and influence consumers. This is especially true when targeting a specific group or one with cultural ties, where an advertisement must be meticulously designed to elicit a positive response. This study investigates the influence of advertising antecedent factors on consumer advertising attitude towards the 2025 Ultra Milk Ramadan advertisement. This research identifies five advertising antecedent factors: entertainment, credibility, informativeness, good for economy, and irritation. Furthermore, this study examines the impact of consumers' religio-spiritual insights on advertising attitude, given that Muslim consumers are the primary target audience for this advertisement, set against the backdrop of a religious festival (such as the holy month of Ramadan). Methods: The research model is based on the Theory of Reasoned Action (TRA). This study adopts a quantitative method using Covariance-Based Structural Equation Modeling (CB-SEM) with AMOS 22 software. Primary data was collected through questionnaires distributed via non-probability (judgmental sampling) involving 300 Muslim consumer respondents in Java. Findings: This study finds that two factors significantly influence advertising attitude: entertainment (β = 0.235, t = 1.971, p = 0.049) and informativeness (β = 0.782, t = 3.918, p = <0.001). Conclusion: It is crucial for businesses to design their advertisements to be engaging and to ensure the information contained within them is readily comprehensible to consumer audiences, especially when targeting Muslim consumers during religious festivals. Novelty/Originality of this article: This research focused on Muslim consumers in Indonesia as its respondents, with the Ultra Milk Ramadan 2025 advertisement functioning as the primary research stimulus.